(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2020)
We report a unique case of prolonged acute rhabdomyolysis in a 2-year-old male with known TANGO-2 mutation with delayed peak in creatinine kinase levels secondary to human metapneumovirus infection. Creatinine kinase peaked at 424,760 U/l on day 9 of hospitalization. Resolution of rhabdomyolysis was achieved using aggressive management with intravenous fluids with optimal urine output and no kidney injury. TANGO-2 patients may develop severe and prolonged rhabdomyolysis with a delayed peak suggesting the need for prolonged inpatient hospitalization to prevent life-threatening complications.